High-Fat Diet Aggravates the Intestinal Barrier Injury via TLR4-RIP3 Pathway in a Rat Model of Severe Acute Pancreatitis - Ying-ru Su; Yu-pu Hong; Fang-chao Mei; Chen-yang Wang; Man Li; Yu Zhou; Kai-liang Zhao; Jia Yu; Wei-xing Wang (Mediators of Inflammation)
Objective. For patients with severe acute pancreatitis (SAP), a high body mass index (BMI) increases the possibility of infection derived from the intestine. In this study, we evaluate whether TAK242 can alleviate severe acute pancreatitis-associated injury of intestinal barrier in high-fat diet-fed rats. Methods. A SAP model was established by retrograde injection of 5% sodium taurocholate into the biliary-pancreatic duct. Thirty Sprague-Dawley (SD) adult rats were randomly divided into five groups: standard rat chow (SRC) normal (SN), SRC SAP (SAP), high-fat diet normal (HN), HFD SAP (HSAP), and TLR4 inhibitor pretreatment HFD SAP (HAPT) groups. Intraperitoneal injection of 3 mg/kg TAK242 was administered 30 minutes before SAP model establishment in the HAPT group. Rats were sacrificed 12 hours after SAP modeling, followed by blood and pancreatic and distal ileum tissue collection for further analyses. Changes in the pathology responses of the rats in each group were assessed. Result. Analyses of serum amylase, lipase, cholesterol, triglyceride, IL-1β, IL-6, DAO, and serum endotoxin as well as tight junction protein expression including zonula occluden-1 and occludin indicated that high-fat diet aggravated SAP-induced intestinal barrier injury via increasing inflammatory response. In addition, the level of necroptosis was significantly higher in the SAP group compared with the SN group while the HSAP group exhibited more necroptosis compared with the SAP group, indicating the important role of necroptosis in pancreatitis-associated gut injury and illustrating that high-fat diet aggravated necroptosis of the ileum. Pretreatment with TLR4 inhibitor significantly alleviated inflammatory response and reduced necroptosis and level of oxidative stress while improving intestinal barrier function. Conclusion. High-fat diet aggravated SAP-induced intestinal barrier injury via inflammatory reactions, necroptosis, and oxidative stress. Inhibition of TLR4 by TAK242 reduced inflammation, alleviated necroptosis, and lowered the level of oxidative stress and then protected the intestinal barrier dysfunction from SAP in high-fat diet-fed rats.